Analysis Of Determinant Factors Quality Of Financial Reporting Of Regional Financial Management Work Units In Indonesia - Prakoso, Teguh; Rina Apriliani; Pandu Adi Cakranegara; Alfiana; Ratnawita (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This study intends to investigate the effects on the quality and value of financial report information of human resource quality, internal control systems, government accounting standards implementation, use of regional financial accounting information systems, and accounting knowledge. This study examines relationships between causes and effects. Questionnaires are used to collect data. The research's population consists of all employees who have employed information systems to do their jobs. With a sample size of 100, the sampling strategy is non-probability sampling. Multiple linear regression analysis was employed as the analytical technique in this study. The study's result demonstrates that a number of variables have varying effects on the informational usefulness and quality of regional financial reports. First off, there isn't much of an impact from the caliber of human resources. Furthermore, there is no notable impact from the internal control system. Third, the information value and quality of regional financial reports are greatly impacted by the use of government accounting rules. Fourth, there is no discernible impact from using regional financial accounting information systems. Fifth, the informational value of regional financial reports is greatly impacted by one's grasp of accounting. Overall, each of these variables affects regional financial reports' information value and quality at the same time, highlighting the need of effective management in these areas for raising the caliber of regional financial data.